1999
DOI: 10.1002/(sici)1097-0185(19990201)254:2<269::aid-ar13>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroids and ultimobranchial bodies in monotremes

Abstract: Only scant information is available in the scientific literature on the parathyroids and ultimobranchial bodies in the primitive mammals, the echidna (Tachyglossus aculeatus) and platypus (Ornithorhynchus anatinus). The major aim of this paper is to describe the morphology of the monotreme parathyroid gland and to compare it with parathyroids in mammals and reptiles. The gross anatomy and light microscopic structure of the ultimobranchial body, thymus, and thyroid are also given. Animals were dissected and rou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…In most vertebrates, two thyroid lobes are positioned cranial to the aortic arch, midway along the carotid arteries, as is the case in mice and humans (Pischinger, 1937). Conversely, in some vertebrates such as crocodiles, turtles, and certain mammals as the echidna (Haynes, 1999;Pischinger, 1937), a single-lobed thyroid is positioned further caudally at the aortic arch, at the base of the branching carotid arteries (Fig. 6).…”
Section: Discussionmentioning
confidence: 99%
“…In most vertebrates, two thyroid lobes are positioned cranial to the aortic arch, midway along the carotid arteries, as is the case in mice and humans (Pischinger, 1937). Conversely, in some vertebrates such as crocodiles, turtles, and certain mammals as the echidna (Haynes, 1999;Pischinger, 1937), a single-lobed thyroid is positioned further caudally at the aortic arch, at the base of the branching carotid arteries (Fig. 6).…”
Section: Discussionmentioning
confidence: 99%
“…We have so far clarified the primary structure of the calcitonin of the stingray, goldfish, sardine and bullfrog by the purification technique of peptides (Takei et al, 1991;Sasayama et al, 1992 andSuzuki et al, 1994;Yoshida et al, 1997). We have also reported the nucleotide sequence of the calcitonin of 4 species of primitive bony fishes, 6 species of amphibians, and 4 species of reptiles by PCR, RT-PCR and RACE-PCR methods 1999;Sakamoto et al, 1999). These studies have demonstrated that calcitonin of primitive bony fish such as lungfish has been conserved from fishes to reptiles and that reptile calcitonin is almost the same as that of chicken.…”
Section: Calcitonin Of the Primitive Bony Fish Is Conserved From Fishmentioning
confidence: 95%
“…Recently, in monotremes: namely the platypus (Orinithorhynchus anatinus) and the echidna (Tachyglossus acleatus), the anatomy and morphology of the ultimobranchial glands, the thyroid gland, and the parathyroid glands were studied (Haynes, 1999). In these animals, one pair of the parathyroid glands did not connect to the thyroid gland but to the thymus, which is one of the characteristics of reptiles.…”
Section: Physiological Demands For Ca Homeostasismentioning
confidence: 99%
“…Exceptionally, in monotremes, the most primitive subclass of mammals, the ultimobranchial body does not integrate into the thyroid primordium. Instead, it remains as a discrete organ lateral to the first or second ring of the cartilaginous trachea, just caudal to the larynx (Haynes, ). The ultimobranchial gland of monotremes consists of a mass of cells and small follicles.…”
Section: Phylogenic Analysis Of the Ultimobranchial Glandmentioning
confidence: 99%